Enamel steel sheet and method for manufacturing the same

CN116529406BActive Publication Date: 2026-10-23POHANG IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180075041.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-05
Filing Date
2021-11-04
Publication Date
2026-10-23
Estimated Expiration
2041-11-04

AI Technical Summary

Benefits of technology

[0039]根据本发明的一实施例的抗鳞爆性和搪瓷附着性优异的搪瓷用钢板,可以用于家电、化工设备、厨房设备、卫浴设备和建筑内外饰材料等。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116529406B_ABST
    Figure CN116529406B_ABST
Patent Text Reader

Abstract

A steel sheet for enamel according to an embodiment of the present application contains, in mass%, C: 0.01 to 0.05%, Mn: 0.05 to 0.8%, Si: 0.001 to 0.03%, Al: 0.03 to 0.12%, P: 0.001 to 0.02%, S: 0.001 to 0.02%, N: 0.004% or less except 0%, B: 0.001 to 0.003%, and O: 0.003% or less except 0%, with the balance containing Fe and inevitable impurities. A steel sheet for enamel according to an embodiment of the present application contains an oxide layer in a direction from the surface to the inside, and the oxide layer thickness is 0.006 to 0.030 µm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a steel sheet for enamel enamel and a method for manufacturing the same. More specifically, one embodiment of the present invention relates to a continuously annealed steel sheet for enamel enamel processing that does not produce bubble defects after enamel treatment and has excellent enamel adhesion and anti-scaling properties, and a method for manufacturing the same. Background Technology

[0002] Enameled steel sheet is a surface-treated product made by coating a base steel sheet (e.g., hot-rolled or cold-rolled steel sheet) with a glass enamel coating and then sintering it at high temperatures, thereby improving its corrosion resistance, weather resistance, and heat resistance. This type of enamel-lined steel sheet is used in building exteriors, home appliances, tableware, and various industrial materials.

[0003] For a long time, rimmed steel has been used for enamel steel sheets, but recently continuous casting has been actively adopted to improve productivity, so most materials are now being continuously cast. Furthermore, one of the most fatal defects in steel manufacturing for enamel steel sheets is fishscale, a typical enamel defect caused by hydrogen dissolved in the steel being released from a supersaturated state to the steel surface during cooling after sintering, resulting in the enamel layer peeling off in a fish-scale pattern. If such fishscale defects occur, rust will concentrate at the defective sites, significantly reducing the value of the enamel product; therefore, it is necessary to suppress the formation of fishscale defects. To prevent fishscale defects, numerous sites need to be formed inside the steel to accommodate hydrogen dissolved in the steel. Therefore, to prevent fishscale defects that reduce enamel properties or improve aging performance, open coil annealing (OCA), one of the batch annealing methods, is also used. However, in this case, productivity decreases, manufacturing costs increase, and there are significant quality deviations due to the long heat treatment time. Furthermore, the loose-coil annealing method is problematic because it's difficult to control the amount of decarburization. Excessive decarburization, coupled with insufficient carbon in the steel, softens the grain boundaries, leading to cracking and brittle fracture during product forming. To overcome the reduced productivity and increased manufacturing costs caused by prolonged annealing, recently developed enamel steel sheets actively utilize continuous annealing processes. In this process, precipitates such as titanium or inclusions in undeoxidized steel are primarily used as hydrogen adsorption sources. However, even under these conditions, the surface defect rate is high due to the addition of numerous carbonitride-forming elements or undeoxidized compounds. Moreover, the increased recrystallization temperature leads to various quality issues, such as decreased sheet permeability, contributing to both reduced productivity and increased costs.

[0004] In other words, because titanium (Ti)-based enamel steel plates incorporate large amounts of titanium to suppress hydrogen reactions that cause scaling, sprue blockage due to titanium nitrides (TiN) and inclusions frequently occurs during the continuous casting process in steelmaking, directly contributing to decreased operability and reduced production load. Furthermore, the TiN mixed in with the molten steel exists in the upper part of the steel plate, not only causing blister defects (a typical bubble defect), but the large amount of added titanium also impairs the adhesion between the steel plate and the enamel layer.

[0005] On the other hand, even with high-oxygen enamel steel plates that increase the dissolved oxygen content inside the steel plate and utilize inclusions such as oxides in the steel to adsorb hydrogen to ensure resistance to flaking, the high oxygen content already results in extremely severe melting loss of the refractory material. This not only greatly reduces the continuous casting productivity in the steelmaking process but also leads to frequent surface defects. Summary of the Invention

[0006] Technical issues

[0007] One embodiment of the present invention aims to provide a steel sheet for enamel enamel and a method for manufacturing the same. More specifically, one embodiment of the present invention aims to provide a continuously annealed steel sheet for enamel enamel processing that does not produce bubble defects after enamel treatment and has excellent enamel adhesion and anti-scaling properties, as well as a method for manufacturing the same.

[0008] Technical solution

[0009] According to an embodiment of the present invention, the enamel steel sheet comprises, by weight %, C: 0.01 to 0.05%, Mn: 0.05 to 0.80%, Si: 0.001 to 0.03%, Al: 0.03 to 0.12%, P: 0.001 to 0.02%, S: 0.001 to 0.02%, N: less than 0.004% and excluding 0%, B: 0.001 to 0.003%, and O: less than 0.003% and excluding 0%, with the balance comprising Fe and unavoidable impurities.

[0010] According to an embodiment of the present invention, the enamel steel sheet includes an oxide layer from the surface inward, the oxide layer having a thickness of 0.006 to 0.030 μm.

[0011] The oxide layer can contain more than 90% by weight of Fe oxide.

[0012] According to an embodiment of the present invention, the enamel steel plate satisfies the following formula 1.

[0013] [Formula 1]

[0014] 0.002≤(1.4×[B]×[Al]) / [N]≤0.0095

[0015] In Equation 1, [B], [Si], and [N] represent the content of elements B, Si, and N, respectively, divided by (atomic %).

[0016] According to an embodiment of the present invention, the difference in cementite fraction (Cv) after annealing, calculated by the following formula 2, can be from 0.8% to 2.5%.

[0017] [Equation 2]

[0018] Cv = C 1 / 2t -C 1 / 8t

[0019] In Equation 2, C 1 / 2t and C 1 / 8t Each represents the cementite fraction in the center and 1 / 8 portion of the steel plate along its thickness direction.

[0020] According to an embodiment of the present invention, the difference in microcavity area ratio (MVv) of different parts of the enamel steel sheet, calculated by the following formula 3, can be 0.075 to 0.155%.

[0021] [Formula 3]

[0022] MVv = MV 1 / 8t -MV Av

[0023] In Equation 3, MV 1 / 8t and MV Av Each represents the 1 / 8 portion and the average microcavity fraction in the thickness direction.

[0024] According to an embodiment of the present invention, the enamel steel sheet may further contain one or more of Cu: less than 0.01% by weight and Ti: less than 0.005% by weight.

[0025] According to an embodiment of the present invention, the enamel-coated steel plate has an enamel adhesion of 95% or higher.

[0026] According to an embodiment of the present invention, the hydrogen permeability of the enamel-coated steel sheet can be 600 seconds / mm. 2 above.

[0027] A method for manufacturing an enamel steel sheet according to an embodiment of the present invention comprises: hot rolling a slab to manufacture a hot-rolled steel sheet, wherein the slab comprises, by weight %, C: 0.02 to 0.08%, Mn: 0.05 to 0.80%, Si: 0.001 to 0.03%, Al: 0.03 to 0.12%, P: 0.001 to 0.02%, S: 0.001 to 0.02%, N: less than 0.004% and excluding 0%, B: 0.001 to 0.003%, and O: less than 0.003% and excluding 0%, with the balance comprising Fe and unavoidable impurities; cold rolling the hot-rolled steel sheet to manufacture a cold-rolled steel sheet; and annealing the cold-rolled steel sheet.

[0028] The annealing step can be performed in a humid environment with an oxidation capacity index (PH2O / PH2) of 0.51 to 0.65 for 30 to 180 seconds.

[0029] The slab satisfies the following formula 1,

[0030] [Formula 1]

[0031] 0.002≤(1.4×[B]×[Al]) / [N]≤0.0095

[0032] In Equation 1, [B], [Si], and [N] represent the content of elements B, Si, and N, respectively, divided by (atomic %).

[0033] The slab can be hot rolled at a final rolling temperature of 850℃ to 910℃.

[0034] In the process of manufacturing hot-rolled steel sheets, the hot-rolled steel sheets can be coiled at a temperature of 580°C to 720°C.

[0035] In the process of manufacturing cold-rolled steel sheets, cold rolling can be performed at a reduction rate of 60 to 90%.

[0036] In the annealing process of cold-rolled steel sheets, annealing can be carried out at temperatures between 720°C and 850°C.

[0037] After the annealing step of the cold-rolled steel sheet, a temper rolling step with a reduction rate of less than 3% may also be included.

[0038] Invention Effects

[0039] According to an embodiment of the present invention, an enamel-coated steel plate with excellent anti-scaling properties and enamel adhesion can be used in household appliances, chemical equipment, kitchen equipment, bathroom equipment, and building interior and exterior decoration materials, etc.

[0040] According to an embodiment of the present invention, an enamel-enameled steel sheet exhibiting excellent resistance to blistering and enamel adhesion is manufactured by suppressing the chemical composition of the steel within an appropriate range and controlling adhesion-related indices. Therefore, the cold-rolled steel sheet produced can ensure high enamel adhesion. Furthermore, by controlling the carbide and micro-void fractions in the surface layer and the central portion, the fatal defects of blistering and bubble defects in the enamel-enameled steel sheet can be controlled, thereby significantly improving enamel properties.

[0041] According to an embodiment of the present invention, an enamel steel sheet with excellent anti-scaling and enamel adhesion is produced by using low-carbon steel with a C content of 0.02 to 0.08% by weight, which has excellent surface properties during the steelmaking process. This improves productivity and operability. Furthermore, when the cold-rolled sheet is heat-treated in a continuous annealing furnace, the carbide fraction in the steel is controlled in the thickness direction by optimizing the furnace environment, thereby significantly improving the enamel properties even during high-speed heat treatment operations.

[0042] According to an embodiment of the present invention, an enamel-enameled steel sheet exhibiting excellent resistance to blistering and enamel adhesion utilizes cementite, a low-temperature precipitate, to promote decarburization during a continuous annealing process by controlling the environment. The cementite is uniformly dispersed during hot rolling, and the microcavities formed by cold rolling and the decarburization reaction act as hydrogen adsorption sources, thereby preventing hydrogen-induced blistering defects. On the other hand, residual carbon on the surface layer of the steel sheet due to the gasification reaction during enamel sintering can also contribute to bubble defects in enamel products. Therefore, the present invention controls the distribution of carbides and microcavities in the thickness direction of the cold-rolled steel sheet, thereby not only improving enamel properties but also preventing surface bubble defects. Attached Figure Description

[0043] Figure 1 This is a schematic cross-sectional view of an enamel steel plate according to an embodiment of the present invention.

[0044] Figure 2 It is based on the glow discharge spectrum (GDS) analysis results of the enamel steel plate of Invention Example 3 at different depths. Detailed Implementation

[0045] In this specification, the terms "first," "second," "third," etc., are used to describe various parts, components, regions, layers, and / or segments, but these parts, components, regions, layers, and / or segments should not be limited by these terms. These terms are only used to distinguish one part, component, region, layer, and / or segment from another part, component, region, layer, and / or segment. Therefore, without departing from the scope of the invention, the first part, component, region, layer, and / or segment described below can also be described as a second part, component, region, layer, and / or segment.

[0046] In this specification, when a part is described as "containing" a certain element, it means, unless specifically stated to the contrary, that it may also contain other elements, and does not exclude other elements.

[0047] The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. Unless the context clearly indicates otherwise, the singular forms used herein are intended to include the plural forms as well. The word "comprising" as used in this specification can specifically refer to a particular feature, field, integer, step, action, element, and / or component, but does not exclude the presence or addition of other features, fields, integers, steps, actions, elements, components, and / or groups.

[0048] In this specification, "the combination of them" in the Markush form means a mixture or combination of one or more of the constituent elements described in the Markush form, implying that it includes one or more of the constituent elements described above.

[0049] In this specification, if a part is described as being on top of another part, then other parts may exist directly on top of or in between the other part. When a part is described as being directly on top of another part, there are no other parts in between.

[0050] Although not otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Terms defined in dictionaries should be interpreted as having the same meaning as disclosed in relevant technical literature and herein, and should not be interpreted in an idealized or overly formal sense.

[0051] Additionally, unless otherwise specified, % indicates weight, and 1 ppm is 0.0001 wt%.

[0052] In one embodiment of the present invention, the inclusion of an additional element means that a portion of the remaining iron (Fe) is replaced by an additional element, the amount of which is equivalent to the amount of the additional element added.

[0053] Embodiments of the present invention will be described in detail below to enable those skilled in the art to implement the invention. However, the invention can be implemented in various different ways and is not limited to the embodiments described herein.

[0054] According to an embodiment of the present invention, the enamel steel sheet comprises, by weight %, 0.02 to 0.08% C, 0.05 to 0.80% Mn, 0.001 to 0.03% Si, 0.03 to 0.12% Al, 0.001 to 0.02% P, 0.001 to 0.02% S, 0.001 to 0.02% N, less than 0.004% and excluding 0%, B, 0.001 to 0.003% O, and the balance comprising Fe and unavoidable impurities.

[0055] First, explain the reasons for restricting the composition of the steel plate.

[0056] C: 0.01 to 0.05% by weight

[0057] When excessive carbon (C) is added, the strength of the steel increases due to the increased amount of dissolved carbon. However, this hinders the development of texture during annealing, leading to poor formability and blister defects caused by blistering in the enamel layer. On the other hand, if too little C is added, the fraction of carbides that serve as sites for hydrogen adsorption in the steel decreases, making it prone to scaling defects.

[0058] The carbon content in the slab can be from 0.02 to 0.08% by weight. More specifically, the carbon content in the slab can be from 0.024 to 0.076% by weight.

[0059] Regarding the manufacturing process described later, during the final annealing process, due to decarburization occurring in an environment with a high oxidation index, the carbon content in the slab and the final steel plate will differ. Since decarburization proceeds to approximately 0.01 to 0.05% by weight, the carbon content in the final steel plate can be 0.01 to 0.05% by weight. The carbon content in the final steel plate can have a concentration gradient along the thickness direction, and the aforementioned carbon content represents the average carbon content throughout the steel plate 100 with oxide layer 20. More specifically, the carbon content in the final steel plate can be 0.015 to 0.045% by weight.

[0060] Mn: 0.05 to 0.80% by weight

[0061] Manganese (Mn), as a typical solid solution strengthening element, causes dissolved sulfur in steel to precipitate as manganese sulfide (MnS), thereby preventing hot shortness and promoting carbide precipitation. If the amount of Mn added is too small, the aforementioned effects are difficult to achieve. On the other hand, if the Mn content is too large, it leads to poor formability and lowers the Ar3 transformation temperature, potentially causing deformation during enamel sintering. Therefore, Mn can be contained in quantities of 0.05 to 0.80% by weight. More specifically, Mn can be contained in quantities of 0.05 to 0.60% by weight. More specifically, Mn can be contained in quantities of 0.10 to 0.40% by weight.

[0062] Si: 0.001 to 0.03% by weight

[0063] Silicon (Si) is an element that promotes the formation of carbides that act as a hydrogen adsorption source. If too little Si is added, the aforementioned effects are difficult to achieve. On the other hand, if too much Si is added, the formation of an oxide film on the steel plate surface may reduce enamel adhesion. Therefore, Si can be contained in the form of 0.001 to 0.030% by weight. More specifically, it can be contained in the form of 0.002 to 0.027% by weight.

[0064] Al: 0.03 to 0.12% by weight

[0065] Aluminum (Al) acts as a strong deoxidizer in the steelmaking process, removing oxygen from molten steel and fixing dissolved nitrogen, thereby improving aging performance. If too little Al is added, the aforementioned effects are difficult to achieve. On the other hand, if too much Al is added, the alumina present in or on the surface of the steel may cause defects such as blistering during the enamel finishing process. Therefore, Al can be contained in quantities of 0.03 to 0.12% by weight. More specifically, it can be contained in quantities of 0.035 to 0.115% by weight.

[0066] P: 0.001 to 0.020% by weight

[0067] Phosphorus (P) is a typical material strengthening element. If the amount of P added is too small, the aforementioned effects will be difficult to achieve. On the other hand, if the amount of P added is too large, it will form a segregation layer inside the steel sheet, which will not only reduce formability but also worsen the pickling properties of the steel and may adversely affect the adhesion of enamel. Therefore, P can be contained in amounts of 0.001 to 0.020% by weight. More specifically, it can be contained in amounts of 0.002 to 0.018% by weight.

[0068] S: 0.001 to 0.020% by weight

[0069] Sulfur (S) is an element that combines with manganese to cause red-hot brittleness. If too little S is added, it can lead to problems with weldability. If too much S is added, it will significantly reduce ductility, resulting in poor workability, and may also adversely affect the scaling properties due to excessive manganese sulfide precipitation. Therefore, S can be contained in amounts from 0.001 to 0.020% by weight. More specifically, it can be contained in amounts from 0.002% to 0.018% by weight.

[0070] N: less than 0.004% by weight

[0071] Nitrogen (N) is a typical hardening element, but if its addition increases, aging defects occur frequently, and formability deteriorates, potentially leading to bubble defects in the enamel finishing process. Therefore, the upper limit of N is limited to 0.004% by weight. More specifically, N can contain 0.0005 to 0.0037% by weight.

[0072] B: 0.001 to 0.003% by weight

[0073] Boron (B) combines with nitrogen in steel to form nitrides, which not only inhibit aging caused by dissolved nitrogen, but the precipitates also serve as a source of hydrogen adsorption within the steel. Boron is an effective element for improving resistance to scaling. While an addition of 0.001% by weight or more is required to achieve the desired effect, excessive addition can harden the material and worsen the annealing process. Boron can be present in a maximum of 0.003% by weight. More specifically, it can be present in 0.0013 to 0.0027% by weight.

[0074] O: less than 0.003% by weight

[0075] Oxygen (O) is an essential element for the formation of oxides, which not only cause refractory loss during the steelmaking process but also contribute to surface defects caused by surface oxides during steel plate manufacturing. Therefore, the amount of O added to the slab can be less than 0.003% by weight. More specifically, the slab can contain 0.0001 to 0.0019% by weight of O.

[0076] Regarding the manufacturing process described later, during the final annealing process, due to decarburization in an environment with a high oxidation index, some oxygen will penetrate, thereby forming an oxide layer 20. However, the thickness of the oxide layer 20 is very thin relative to the overall steel plate 100, so the oxygen content in the overall steel plate 100 does not change substantially. The oxide layer 20 contains more than 5% by weight of oxygen. More specifically, the oxide layer 20 may contain 10 to 50% by weight of O. The oxygen content in the oxide layer 20 refers to the average content in the oxide layer 20.

[0077] According to an embodiment of the present invention, the enamel steel plate satisfies the following formula 1.

[0078] [Formula 1]

[0079] 0.002≤(1.4×[B]×[Al]) / [N]≤0.0095

[0080] In Equation 1, [B], [Si], and [N] represent the content of elements B, Si, and N, respectively, divided by (atomic %).

[0081] Aluminum and boron in steel react with nitrogen to form nitrides, which improves workability. It is necessary to consider not only the individual elements but also their reactivity with nitrogen. In this case, boron reacts with nitrogen before aluminum, and the atomic ratio defined in Equation 1 needs to be controlled between 0.0020 and 0.0095. If the atomic ratio is too low, workability will deteriorate due to the increased amount of residual dissolved nitrogen in the steel. Conversely, if the atomic ratio is too high, workability and annealing passability may decrease due to material hardening. More specifically, the value of Equation 1 can be between 0.0025 and 0.0090.

[0082] In addition to the components described above, this invention contains Fe and unavoidable impurities, and does not exclude the addition of effective components other than those described above. Unavoidable impurities include, for example, Cu and Ti. In one embodiment of this invention, Cu and Ti are not intentionally added, and the invention may contain less than 0.01% by weight of Cu and less than 0.005% by weight of Ti.

[0083] Next, the rationale for limiting the volume fraction of carbides in the steel sheet and the hot rolling process of this invention will be described. The carbides used in the steel of this invention have different ductility from the base material. During the cold rolling process, the carbides themselves break down, or microvoids are formed through subsequent decarburization heat treatment. Furthermore, the carbides themselves also act as hydrogen adsorption sources for fixing hydrogen in the steel. Therefore, such carbide fraction not only affects enamel properties independently, but also its relationship with added elements. The enamel steel sheet proposed in this invention, by adjusting the steel composition to act as hydrogen adsorption sites, mainly utilizes carbides such as Fe3C (cementite), and actively utilizes microvoids generated by decarburization. Simultaneously, it controls the components and processes in the steel composition that affect enamel adhesion and surface defects, thereby providing enamel steel sheets and products with no surface defects and excellent enamel adhesion and anti-scaling properties. The uniformly dispersed and precipitated cementite during hot rolling breaks down during cold rolling. Furthermore, the annealing process, by controlling the environment as a decarburization reaction source, forms microcavities that act as hydrogen adsorption sources. This effectively fixes hydrogen in the steel, thereby suppressing scaling defects. By controlling the carbide and microcavity fractions in the thickness direction through continuous annealing and decarburization operations, and by controlling the oxide behavior of the steel plate surface layer, it also has a significant effect on enamel adhesion and suppression of bubble defects. On the other hand, unlike high-temperature precipitates / inclusions that form during high-temperature solidification, one embodiment of the present invention utilizes carbides that are stable at low temperatures. This prevents operational degradation such as problematic refractory melting or continuous casting nozzle blockage in existing enamel steels, as well as preventing surface defects such as black lines. The carbide fraction is not only closely related to the total carbon content in the steel, but also has a significant impact from operating conditions. Furthermore, for the steel of the present invention, not only are elements such as titanium (Ti), which have higher oxidizing power than Fe, not added, but by controlling the surface oxide layer, the enamel adhesion between the steel plate and the enamel can be greatly improved.

[0084] Figure 1 The diagram shows a cross-sectional schematic of a steel plate for enamel enamel according to an embodiment of the present invention. Figure 1 As shown, an oxide layer 20 extends from the surface of the steel plate inwards. The oxide layer 20 contains more than 5% by weight of oxygen (O), which distinguishes it from the steel plate substrate 10, which has an oxygen (O) content of less than 5% by weight. Specifically, when analyzing the oxygen concentration from the surface inwards for a cross-section of the steel plate, the oxide layer 20 and the substrate 10 are distinguished based on the location where the oxygen content is 5% by weight. If there are multiple locations with an oxygen content of 5% by weight, the innermost location is used as the distinguishing point.

[0085] The oxide layer 20 may contain more than 90% by weight of Fe oxide.

[0086] Enameled products are made by coating steel plates with organic enamel, so ensuring good adhesion between the steel plate and the enamel is crucial. Typically, the main component of the enamel is silicon dioxide (SiO2). To prevent reduced adhesion to the steel plate, expensive enamels containing large amounts of NiO or similar compounds are often used.

[0087] In one embodiment of the present invention, repeated experiments confirmed that a method to improve enamel adhesion can be achieved by controlling the thickness of the oxide layer on the surface of the steel plate. By controlling the thickness of the oxide layer, which is mainly composed of FeO, within a certain range, covalent bonding with silicon (Si) atoms in the enamel layer is promoted, thereby improving enamel adhesion. For this purpose, the oxide layer thickness needs to be controlled between 0.006 and 0.030 μm. If the oxide layer thickness is too thin, the bonding force between the enamel layer and the steel plate is reduced, making it difficult to ensure enamel adhesion. On the other hand, if the oxide layer thickness is too thick, although it is beneficial to adhesion, there is a problem of deterioration in the surface properties of the steel plate. Therefore, the thickness of the oxide layer 20 on the surface of the steel plate is limited to 0.006 to 0.030 μm. More specifically, the thickness of the oxide layer 20 can be between 0.007 and 0.028 μm. The thickness of the oxide layer 20 may vary on the entire steel plate 100; in one embodiment of the present invention, the thickness of the oxide layer 20 refers to the average thickness relative to the entire steel plate 100.

[0088] According to an embodiment of the present invention, the cementite fraction difference (Cv) of the enamel steel sheet calculated by the following formula 2 can be from 0.8% to 2.5%.

[0089] [Equation 2]

[0090] Cv = C 1 / 2t -C 1 / 8t

[0091] In Equation 2, C 1 / 2t and C 1 / 8tEach represents the cementite fraction in the center and 1 / 8 portion of the steel plate along its thickness direction.

[0092] Carbon in metal alloys combines with metal atoms to form carbides, and one type of carbide formed by the combination of iron and carbon at relatively low temperatures is cementite. In ordinary carbon steel, cementite forms at temperatures between 250 and 700°C, and at even higher temperatures, it coarsens into spherical granules. The cementite generated during the hot rolling process breaks down during cold rolling and decomposes during decarburization, becoming a source of hydrogen adsorption. However, if this cementite is concentrated on the surface of the steel, it becomes a source that promotes carbon vaporization during enamel sintering, and also a factor causing bubble defects. Therefore, to suppress scaling and bubble defects in enamel products, it is necessary to strictly control the carbide volume fraction in the thickness direction. That is, if the cementite fraction difference Cv in the thickness direction of the cold-rolled steel sheet is too small, the decarburization reaction will not proceed smoothly, thus increasing the carbide fraction in the surface layer, which becomes a factor causing bubble defects after enamel sintering. On the other hand, if Cv is too large, due to insufficient supply of hydrogen adsorption sites in the steel, it is difficult to suppress scaling defects. Therefore, the cementite fraction difference Cv in the thickness direction can be from 0.8% to 2.5%. More preferably, Cv can be from 0.85% to 2.45%.

[0093] According to an embodiment of the present invention, the difference in microcavity area ratio (MVv) of different parts of the enamel steel sheet, calculated by the following formula 3, can be 0.075 to 0.155%.

[0094] [Formula 3]

[0095] MVv = MV 1 / 8t -MV Av

[0096] In Equation 3, MV 1 / 8t and MV Av Each represents the 1 / 8 portion and the average microcavity fraction in the thickness direction.

[0097] Cementite precipitated during hot rolling breaks down during cold rolling and decarburization heat treatment, forming microcavities around it. These microcavities become hydrogen adsorption sources, thus suppressing the formation of blistering defects. For microcavities in cold-rolled steel sheets, ten images were taken at 1000x magnification using a scanning electron microscope on the surface parallel to the rolling face (ND face), and the area fraction of microcavities in these areas was measured using an image analyzer. In one embodiment of the invention, by controlling the area fraction distribution of these microcavities in different locations, regions capable of simultaneously suppressing blistering and bubble defects were identified. To ensure this effect, the microcavity area fraction difference MVv needs to be controlled between 0.075 and 0.155%. If the microcavity area fraction difference MVv is too small, although it is beneficial for anti-blistering, it leads to problems such as deterioration of workability and frequent surface defects such as bubble defects. On the other hand, if MVv is too large, the number of sites in the steel that can fix hydrogen and become hydrogen adsorption sources decreases, which may lead to a higher rate of blistering defects in the product. Therefore, the microcavity area ratio difference MVv is limited to 0.075% to 0.155%. More specifically, MVv can be 0.080% to 0.150%.

[0098] According to one embodiment of the present invention, the enamel adhesion of the steel sheet can be 95% or higher. By satisfying this property, it can be used as an enamel material even using relatively inexpensive enamels. If the enamel adhesion is excessively reduced, the enamel layer will peel off during distribution or handling after enamel processing, reducing its marketability as an enamel material. Therefore, enamel manufacturers, considering stability, use expensive enamels with large amounts of components such as NiO, thus increasing costs. Therefore, efforts are being made to develop a scheme that ensures enamel adhesion even when using inexpensive enamels. Generally, an enamel adhesion of 90% or higher is considered optimal for enamel products, but one embodiment of the present invention proposes a scheme that ensures an enamel adhesion of 95% or higher. Furthermore, if the enamel adhesion decreases, the rate of hydrogen-induced scaling in the steel will also increase; therefore, it is preferable to ensure the highest possible adhesion. In the present invention, excellent enamel adhesion of 95% or higher is also ensured in terms of adhesion characteristics and scaling control. More specifically, the enamel adhesion can be 96% or higher. Enamel adhesion refers to the degree of electrical conductivity of an area after a steel ball has been applied to the enamel layer under a certain load, as defined in ASTM C313-78 of the American Society for Testing and Materials, and is expressed by indexing the degree of enamel enamel layer peeling off.

[0099] According to one embodiment of the present invention, the hydrogen permeability of the enamel-coated steel sheet can be 600 seconds / mm. 2The above. Hydrogen permeability is a typical index for evaluating resistance to blistering, which represents the resistance of enamel steel made from cold-rolled steel sheet according to an embodiment of the present invention to the fatal defect of blistering. The ability of the steel sheet to fix hydrogen is evaluated by a method included in European Standard (EN10209). This is measured by the time (t) it takes for hydrogen to permeate from one direction of the steel sheet to the opposite direction after hydrogen is generated in that direction. s The value is expressed as t (the unit is seconds) divided by the square of the material thickness (t, unit is mm). s / t 2 (Unit: seconds / mm) 2 If the hydrogen permeability is too low, the defect rate exceeds 50% when evaluating the resistance to blistering defects after enamel treatment and accelerated heat treatment at 200℃ for 24 hours, posing a problem for use as a stable enamel product. Therefore, to ensure steel plates with excellent resistance to blistering, the hydrogen permeability needs to be controlled at 600 seconds / mm². 2 That's all. Furthermore, more specifically, the hydrogen permeability can be 610 seconds / mm. 2 above.

[0100] A method for manufacturing an enamel steel sheet according to an embodiment of the present invention comprises: hot rolling a slab to manufacture a hot-rolled steel sheet, wherein the slab comprises, by weight %, C: 0.02 to 0.08%, Mn: 0.05 to 0.8%, Si: 0.001 to 0.03%, Al: 0.03 to 0.12%, P: 0.001 to 0.02%, S: 0.001 to 0.02%, N: less than 0.004% and excluding 0%, B: 0.001 to 0.003%, and O: less than 0.003% and excluding 0%, with the balance comprising Fe and unavoidable impurities; cold rolling the hot-rolled steel sheet to manufacture a cold-rolled steel sheet; and annealing the cold-rolled steel sheet.

[0101] First, prepare slabs that meet the aforementioned composition requirements. For molten steel whose composition has been adjusted to the aforementioned composition during the steelmaking process, slabs can be produced by continuous casting. As mentioned earlier, the C and O contents will change somewhat during the annealing process of cold-rolled steel sheets, while other alloying components are essentially the same as those for enamel steel sheets. The alloying composition has already been described, so a repetition is omitted.

[0102] The manufactured slab is then heated. Heating facilitates subsequent hot rolling processes and homogenizes the slab. More specifically, heating can be reheating.

[0103] At this point, the slab heating temperature can be between 1150 and 1280°C. If the slab heating temperature is too low, the rolling load in the subsequent hot rolling process will increase sharply, which may lead to poor operability. On the other hand, if the slab heating temperature is too high, not only will energy costs increase, but the amount of surface oxide scale will also increase, which may lead to material loss. More specifically, it can be between 1180 and 1260°C.

[0104] Then, the heated slab is hot-rolled to produce hot-rolled steel sheets.

[0105] At this point, the final hot rolling temperature can be between 850 and 910°C. If the final hot rolling temperature is too low, grain mixing will occur rapidly due to ending rolling in the low-temperature region, potentially leading to reduced rollability and processability. On the other hand, if the final hot rolling temperature is too high, the peelability of the surface oxide scale will decrease, and the hot rolling will not be uniform across the entire thickness, which may result in grain growth and reduced impact toughness. More specifically, the final hot rolling temperature can be between 860 and 900°C.

[0106] Then, the hot-rolled steel sheet produced after hot rolling will undergo a coiling process. More specifically, it can be a hot-rolled coiling process.

[0107] At this point, the coiling temperature can be between 580 and 720°C. The hot-rolled steel sheet can be cooled on the run-out table (ROT) before coiling. If the hot-rolling coiling temperature is too low, uneven temperature distribution in the width direction occurs during the cooling and holding process, leading to changes in the formation of low-temperature precipitates. This not only causes material deviations but also negatively impacts enamel properties. On the other hand, if the coiling temperature is too high, the formation of carbides reduces corrosion resistance and promotes grain boundary segregation of phosphorus, resulting in reduced cold rollability and coarser microstructure in the product, leading to poorer processability. More specifically, the coiling temperature can be between 590 and 710°C.

[0108] Before cold rolling the coiled hot-rolled steel sheet, a pickling step may be included.

[0109] Then, the hot-rolled steel sheet is cold-rolled into cold-rolled steel sheet.

[0110] At this point, the cold rolling reduction rate can be 60% to 90%. If the cold rolling reduction rate is too low, the recrystallization driving force in the heat treatment process is not ensured, resulting in localized residual unrecrystallized grains, leading to increased strength but significantly reduced processability. Furthermore, due to the reduced breakage ability of carbides formed during the hot rolling step, the number of sites capable of adsorbing hydrogen decreases, making it difficult to ensure resistance to scaling. Moreover, considering the final product thickness, the thickness of the hot-rolled plate needs to be reduced, thus worsening rolling operability. On the other hand, if the cold rolling reduction rate is too high, material hardening not only worsens processability but also increases the load on the rolling mill, resulting in decreased operability. More specifically, the cold rolling reduction rate can be 63% to 88%.

[0111] Then, enamel steel sheets are manufactured by continuously annealing the cold-rolled steel sheets. Cold-rolled materials, due to the high deformation during cold rolling, have high strength but extremely poor machinability. Therefore, heat treatment is performed in subsequent processes to ensure machinability and decarburization reaction.

[0112] In one embodiment of the invention, during the heat treatment of cold-rolled steel sheets, the oxidation capacity (PH2O / PH2) conditions are controlled to optimize the diffusion rate of carbon atoms, thereby promoting the outward diffusion of carbon atoms in the material and improving decarburization. To this end, based on the optimized management standards for decarburization annealing processes, the decarburization temperature is set in the range of 720 to 850°C, and heat treatment is performed in a humid environment with an oxidation capacity (PH2O / PH2) of 0.51 to 0.65, with an appropriate holding time of 20 to 180 seconds.

[0113] At this point, the heat treatment temperature can be between 720 and 850°C. If the decarburization annealing temperature is too low, the deformation formed by cold rolling will not be sufficiently removed, resulting in a significant reduction in workability. Furthermore, the decarburization rate due to environmental heat treatment will be too low, thus failing to ensure the intended characteristics of the cold-rolled steel sheet for enamel. On the other hand, if the heat treatment temperature is too high, softening due to reduced high-temperature strength will lead to sheet cracking, resulting in reduced annealing permeability. Moreover, the increased thickness of the surface oxide layer will inhibit the decarburization reaction. Therefore, the heat treatment temperature is limited to between 720 and 850°C. More preferably, the annealing temperature can be between 730 and 840°C.

[0114] At this point, the oxidizing power (PH2O / PH2) of the heat treatment environment can be between 0.51 and 0.65. If the oxidizing power is too low, decarburization will take a long time, and the decarburization performance will deteriorate during continuous annealing, making it difficult to ensure the enamel properties. On the other hand, if the oxidizing power is too high, there will be a problem of a high rate of surface defects caused by the surface film formed by over-oxidation. Therefore, the oxidizing power of the ambient gas is limited to 0.51 to 0.65. More specifically, the oxidizing power can be between 0.52 and 0.64.

[0115] Furthermore, the soaking time in the continuous annealing process can be from 20 to 180 seconds. If the soaking time at the holding temperature is too short, unrecrystallized grains will remain, significantly reducing formability and hindering the decarburization reaction in the thickness direction, thus contributing to poor enamel properties. On the other hand, if the holding time is too long, abnormal grain growth will occur due to the decarburization reaction, leading to reduced processability and deterioration of the scaling performance caused by material inhomogeneity. Therefore, the soaking time at the soaking temperature can be from 20 to 180 seconds. More preferably, it can be from 25 to 160 seconds.

[0116] In addition to the annealing step of cold-rolled steel sheet, a temper rolling step can also be included. Temper rolling allows control of the material's shape and the attainment of the desired surface roughness. However, if the temper reduction rate is too high, work hardening can occur, leading to material hardening and decreased machinability. Therefore, temper rolling can employ a reduction rate of less than 3%. Specifically, the reduction rate in temper rolling can be between 0.3% and 2.5%.

[0117] The invention will be further described in detail below by way of examples. However, the following examples are merely for illustrating the invention in more detail and are not intended to limit the scope of the invention. This is because the scope of the invention depends on the content described in the claims and what can be reasonably inferred therefrom.

[0118] Example

[0119] Slabs were manufactured using an alloy composition comprising the components listed in Table 1 (wt%), with the balance being iron (Fe) and unavoidable impurities, via a converter-secondary refining-continuous casting process. The slabs were then hot-rolled after being held in a furnace at 1200°C for 1 hour. The final thickness of the hot-rolled steel sheet was 4.0 mm. After hot rolling, the oxide film on the surface of the samples was removed by pickling, followed by cold rolling at a reduction rate. The cold-rolled samples were then processed into enamel-treated samples for investigating enamel properties and samples for mechanical property analysis, and subsequently subjected to heat treatment. The final hot rolling temperature, coiling temperature, cold rolling reduction rate, annealing temperature, holding time, and oxidation capacity are shown in Table 2.

[0120] The operability, enamel properties, and microstructure of the materials, ensured by the process described above, under different manufacturing conditions are shown in Table 3 below.

[0121] For plate performance, in continuous casting, hot rolling and cold rolling processes, if the workability is above 90% compared to the productivity of general materials, it is indicated as "O"; if the productivity is below 90% or the defect rate is above 10%, it is indicated as "X".

[0122] For the carbide fraction, after ensuring images of 20 fields of view at 500x magnification using an optical microscope, the carbide fraction relative to the entire field of view area was determined using an image analyzer.

[0123] For enamel-treated samples, they were cut to appropriate sizes according to different applications to meet the test objectives. After complete degreasing, the heat-treated samples were coated with a standard enamel (Check frit) less susceptible to blistering defects and held at 300°C for 10 minutes to remove moisture. The dried samples were then sintered at a lower temperature of 800°C for 20 minutes to highlight differences in enamel properties such as adhesion, and then cooled to room temperature. The sintering furnace was subjected to harsh conditions with a dew point temperature of 30°C, which easily leads to blistering defects. Accelerated blistering tests were then conducted on the enamel-treated samples in an oven at 200°C for 24 hours.

[0124] After the accelerated scaling treatment, visually inspect whether scaling defects have occurred. If no scaling defects have occurred, it is marked as "O"; if scaling defects have occurred, it is marked as "X".

[0125] For evaluating the adhesion between the steel plate and the enamel, enamel adhesion is assessed using the method defined in ASTM C313-78, which involves applying a load to the enamel layer with a steel ball and evaluating the electrical conductivity of the area. This indexes the degree of enamel enamel layer detachment, thus representing enamel adhesion. In this invention, from the viewpoint of ensuring stability in the use of cheaper enamels, the target for enamel adhesion is set to ensure an enamel adhesion rate of over 95%.

[0126] For bubble defects, the enamel surface of the samples after enamel treatment and maintenance in an oven at 200°C for 24 hours was visually observed and evaluated using a three-step approach: “O” (excellent), “△” (average), and “X” (poor).

[0127] Hydrogen permeability, as one of the indices for evaluating resistance to the fatal defect of enamel spalling, is measured by an experimental method recorded in European standard (EN10209-2013) that measures the time (t) it takes for hydrogen to permeate from one direction of a steel sheet to the opposite direction after hydrogen is generated in one direction. s The value is expressed as t (the unit is seconds) divided by the square of the material thickness (t, unit is mm). s / t 2 (Unit: seconds / mm) 2 ).

[0128] Table 1

[0129]

[0130]

[0131] Table 2

[0132]

[0133]

[0134] Table 3

[0135]

[0136]

[0137] As shown in Tables 1 to 3, Examples 1 to 9 of the present invention, which satisfy the requirements for component composition, manufacturing conditions, and oxide layer thickness, not only exhibit excellent plate permeability, but also meet the limitations of the present invention in terms of carbide content, micro-void fraction, and related indices. Even under harsh processing conditions, no enamel defects such as blistering and bubble defects are generated. Furthermore, the enamel adhesion is above 95%, and the hydrogen permeability is 600 seconds / mm. 2 The above ensures the target characteristics of the present invention.

[0138] On the other hand, although the chemical composition proposed in this invention is met, Comparative Examples 1 to 4 do not meet the oxidation capacity and time range during final annealing. Due to the lack of proper oxide layer formation, the target characteristics cannot be ensured. As shown in Table 3, the distribution of microvoids also exceeds the management standards. Therefore, the hydrogen permeability is lower than the target (Comparative Examples 1 to 4), or the enamel adhesion is less than 95% (Comparative Examples 1 to 4), or enamel defects such as bubble defects or blistering occur after enamel treatment. Overall, the target characteristics cannot be ensured.

[0139] Comparative Examples 5 to 9 met the manufacturing conditions proposed in this invention, but did not meet the alloy composition requirements. Most of Comparative Examples 5 to 9 did not meet the management standards of this invention regarding cementite and microvoid area fraction in different thickness directions, surface oxide layer thickness, adhesion index, hydrogen permeability, enamel adhesion, etc., and scaly or bubble defects were observed in visual inspection after enamel treatment, thus raising applicability issues.

[0140] Figure 2 The image shows the GDS analysis results for different thicknesses of the enamel steel sheet according to Example 4 of the invention. The innermost location with an oxygen content of 5% by weight is 0.016 μm, confirming the presence of an oxide layer 20 with a thickness of 0.016 μm on the surface.

[0141] This invention can be implemented in various ways and is not limited to the embodiments described above. Those skilled in the art will understand that the invention can be implemented in other specific ways without altering its technical concept or essential features. Therefore, it should be understood that the above embodiments are exemplary in all respects and are not restrictive.

[0142] Explanation of reference numerals in the attached figures

[0143] 100: Steel plate for enamel 10: Steel plate substrate

[0144] 20: Oxide layer

Claims

1. A steel plate for enamel enamel, wherein, The steel plate, by weight percent, comprises C: 0.01 to 0.05%, Mn: 0.05 to 0.8%, Si: 0.001 to 0.03%, Al: 0.03 to 0.12%, P: 0.001 to 0.02%, S: 0.001 to 0.02%, N: less than 0.004% and excluding 0%, B: 0.001 to 0.003%, and O: less than 0.003% and excluding 0%, with the balance including Fe and unavoidable impurities. The surface includes an oxide layer extending inwards, the oxide layer having a thickness of 0.006 to 0.030 μm. The steel plate used for enamel enamel satisfies the following formula 1. The cementite fraction difference Cv, calculated by Equation 2, ranges from 0.8% to 2.5%. Among them, the difference in microcavity area ratio (MVv) at different locations, calculated by Equation 3, ranges from 0.075% to 0.155%. Formula 1 0.002 ≤ (1.4×[B]×[Al]) / [N] ≤ 0.0095 In Equation 1, [B], [Si], and [N] represent the atomic percentage content of elements B, Si, and N, respectively. Formula 2 Cv = C 1 / 2t - C 1 / 8t In Equation 2, C 1 / 2t and C 1 / 8t Each represents the cementite fraction in the center and 1 / 8 portion of the steel plate along its thickness direction. Formula 3 MVv = MV 1 / 8t - MV Av In Equation 3, MV 1 / 8t and MV Av Each represents the 1 / 8 portion and the average microcavity fraction in the thickness direction.

2. The enamel steel plate according to claim 1, wherein, The oxide layer contains more than 90% by weight of Fe oxide.

3. The enamel-coated steel plate according to claim 1, wherein, It also contains one or more of Cu: less than 0.01 wt% and Ti: less than 0.005 wt%.

4. The enamel-coated steel plate according to claim 1 has an enamel adhesion of 95% or higher.

5. The enamel-coated steel plate according to claim 1, wherein the hydrogen permeability is 600 seconds / mm². 2 above.

6. A method for manufacturing a steel plate for enamel enamel, comprising: The step of hot rolling a slab to produce a hot-rolled steel sheet, wherein the slab comprises, by weight %, C: 0.02 to 0.08%, Mn: 0.05 to 0.80%, Si: 0.001 to 0.03%, Al: 0.03 to 0.12%, P: 0.001 to 0.02%, S: 0.001 to 0.02%, N: less than 0.004% and excluding 0%, B: 0.001 to 0.003%, and O: less than 0.003% and excluding 0%, with the balance including Fe and unavoidable impurities; The steps of cold rolling the hot-rolled steel sheet to manufacture cold-rolled steel sheet; and The step of annealing the cold-rolled steel sheet in, The annealing step is a heat treatment at 720°C to 850°C for 20 to 180 seconds in a humid environment with an oxidation capacity index (PH2O / PH2) of 0.51 to 0.

65.

7. The method for manufacturing the enamel steel plate according to claim 6, wherein, The slab satisfies the following formula 1, Formula 1 0.002 ≤ (1.4×[B]×[Al]) / [N] ≤ 0.0095 In Equation 1, [B], [Si], and [N] represent the atomic percentage content of elements B, Si, and N, respectively.

8. The method for manufacturing the enamel steel plate according to claim 6, wherein, The slab is hot-rolled at a final rolling temperature of 850°C to 910°C.

9. The method for manufacturing the enamel steel plate according to claim 6, wherein, In the step of manufacturing hot-rolled steel sheet, the hot-rolled steel sheet is wound at 580°C to 720°C.

10. The method for manufacturing the enamel steel plate according to claim 6, wherein, In the process of manufacturing cold-rolled steel sheets, cold rolling is performed with a reduction rate of 60 to 90%.

11. The method for manufacturing the enamel steel plate according to claim 6, wherein, After annealing the cold-rolled steel sheet, the process further includes a step of temper rolling with a reduction rate of less than 3%.

Citation Information

Patent Citations

  • Works for enameling and enameled products

    CN101517115A

  • Enamel steel sheet for direct glazing and manufacturing method thereof

    CN104775069A